1985
DOI: 10.1111/j.1651-2227.1985.tb10957.x
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Breast Fed and Artificially Fed Infants from Birth to Twelve Months

Abstract: Growth data collected from 394 healthy infants were analysed in relation to feeding practices. Infants were grouped on the basis of sex, if breast fed or artificially fed, and duration of breast feeding. From birth to 3 months, weight gains were similar for boys (2.5 kg) and also for girls (2.3 kg) irrespective of feeding method. From 3 to 6 months weight gains were greater in infants who were artificially fed from birth (2.0 kg both sexes) or breast fed for only a short time (1.9 kg) than for those exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
3

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 19 publications
(13 reference statements)
4
18
1
3
Order By: Relevance
“…In addition it is difficult to compare because of the diversity of methodologies. Some authors have demonstrated that breastfed children have growth deficiencies after three months, [23][24][25][26] while others have demonstrated satisfactory growth among both exclusively and predominantly breastfed children; data that agrees with ours where birth weight was doubled before the fourth month. 5,10,18,27 Without doubt, the optimal weight gain observed in our study is the result of all the support and guidance that the mothers receive on the breastfeeding program, so that feeds are given on demand with the correct technique, the baby latches on correctly and develops sufficient suction to obtain all types of milk, particularly the hindmilk, which is rich in fats and has a high energy value, all of which leads to greater weight gain.…”
Section: Discussionsupporting
confidence: 80%
“…In addition it is difficult to compare because of the diversity of methodologies. Some authors have demonstrated that breastfed children have growth deficiencies after three months, [23][24][25][26] while others have demonstrated satisfactory growth among both exclusively and predominantly breastfed children; data that agrees with ours where birth weight was doubled before the fourth month. 5,10,18,27 Without doubt, the optimal weight gain observed in our study is the result of all the support and guidance that the mothers receive on the breastfeeding program, so that feeds are given on demand with the correct technique, the baby latches on correctly and develops sufficient suction to obtain all types of milk, particularly the hindmilk, which is rich in fats and has a high energy value, all of which leads to greater weight gain.…”
Section: Discussionsupporting
confidence: 80%
“…Os dados da literatura são contraditórios quando se referem a crescimento ou velocidade de crescimento de crianças em aleitamento materno, e a comparação entre eles é difícil devido à diversidade de metodologias. Alguns autores têm demonstrado que crianças em aleitamento materno apresentam deficiência de crescimento após os 3 meses de vida 23,24,25,26 , enquanto outros demonstram ser satisfatório o crescimento das crianças em aleitamento materno tanto exclusivamente quanto predominantemente estes últimos achados são concordantes com os do nosso estudo, onde as crianças duplicaram o peso de nascimento antes do quarto mês de vida 5,10,18,27 .…”
Section: Discussionunclassified
“…The breastfed infants had slightly lower estimated energy intakes than the non-breastfed but this was re¯ected in the fact that they weighed less than non-breastfed infants at 8 months. This degree of difference in weight has been shown by many studies (Hitchcock et al, 1985;Hoffmans et al, 1988;Dewey et al, 1992), however, by the age of 3 y the differences are likely to have disappeared (Paul et al, 1988b). The intakes of nearly all nutrients were higher in non-breastfed than breastfed infants with the exception of dietary cholesterol and NSP.…”
Section: Infant Food and Nutrient Intake S Noble And P Emmettmentioning
confidence: 92%